The Effect of Economic Factors, Health Conditions, and Access to Education on Social Inequality and Poverty in West Papua - Iwan Harsono; Himawan Sutanto; Subhan Purwadinata; Endang Astuti; Ahmad Zaenal Wafik (West Science Social and Humanities Studies, 2024)
This research investigates the complex interplay of economic factors, health conditions, and access to education on social inequality and poverty in West Papua through a quantitative analysis. The study, conducted with a sample of 150 participants, employs correlation and regression analyses, supported by SPSS, to unveil significant relationships and dynamics within the socio-economic landscape of the region. Key findings reveal a strong negative correlation between income distribution and poverty rates, emphasizing the pivotal role of economic factors in poverty alleviation. Additionally, a positive correlation between disease prevalence and social inequality underscores the impact of health disparities on socio-economic outcomes. The study also highlights the transformative potential of education, with a robust positive correlation between school enrollment rates and economic well-being. These findings have direct implications for policy formulation, emphasizing the need for integrated approaches that address the synergies and trade-offs among economic, health, and education indicators. The study contributes substantively to the discourse on social inequality and poverty in West Papua, providing empirical evidence to guide evidence-based decision-making.